A low-cost affinity purification system using β-1,3-glucan recognition protein and curdlan beads - Horiuchi, Masataka (Oxford University Press, 2012)
Silkworm β-1,3-glucan recognition protein (βGRP) tightly and specifically associates with β-1,3-glucan. We report here an affinity purification system named the ‘GRP system’, which uses the association between the β-1,3-glucan recognition domain of βGRP (GRP-tag), as an affinity tag, and curdlan beads. Curdlan is a water-insoluble β-1,3-glucan reagent, the low cost of which (about 100 JPY/g) allows the economical preparation of beads. Curdlan beads can be readily prepared by solubilization in an alkaline solution, followed by neutralization, sonication and centrifugation. We applied the GRP system to preparation of several proteins and revealed that the expression levels of the GRP-tagged proteins in soluble fractions were two or three times higher than those of the glutathione S-transferase (GST)-tagged proteins. The purity of the GRP-tagged proteins on the curdlan beads was comparable to that of the GST-tagged proteins on glutathione beads. The chemical stability of the GRP system was more robust than conventional affinity systems under various conditions, including low pH (4–6). Biochemical and structural analyses revealed that proteins produced using the GRP system were structurally and functionally active. Thus, the GRP system is suitable for both the large- and small-scale preparation of recombinant proteins for functional and structural analyses.